A posterior trans-intervertebral osteotomy with anterior support for kyphosis deformity secondary to ankylosing spondylitis: a technical note - Zihao Ding; Yunsheng Wang; Nan Kang; Yong Hai; Lijin Zhou (BMC Musculoskeletal Disorders)
Abstract Background This study aimed to assess the efficacy of a novel spinal osteotomy technique, the posterior trans-intervertebral osteotomy with anterior support, in individuals diagnosed with ankylosing spondylitis. This study utilized computer software to simulate the osteotomy procedure, predict orthopedic outcomes, and assist in preoperative planning. Methods Four patients with ankylosing spondylitis underwent posterior trans-intervertebral osteotomy with anterior support that post-operative follow-up of more than 1 year. Osteotomy was performed using the intervertebral space approach with the cage placed anteriorly in the intervertebral space to improve the correction. Perioperative clinical symptoms, imaging data, and surgical factors were also documented. Results Patients who underwent posterior trans-intervertebral osteotomy with anterior support achieved good clinical results with favorable correction rates and minimal estimated blood loss. The average preoperative, postoperative and follow-up Cobb angles were 90.5° (range: 86–96°), 43.5° (range: 34–52°) and 46.25°(range: 37–55°), respectively. The average estimated blood loss was 500 mL (range: 300–800 mL). Patients with preoperative deficits improved their neurological status, and no complications were observed throughout the postoperative period. Pain, self-image, and mental health in the SRS-22 demonstrated significant improvement at the final follow-up compared to preoperative values. The satisfaction with management score was 3.25 ± 0.65. Conclusions Posterior trans-intervertebral osteotomy with an anterior support procedure was performed through the intervertebral space and subsequent implantation of a cage within the transpedicular space, effectively addressing the constraints associated with the conventional trans-intervertebral osteotomy method. Our preliminary findings indicate that posterior trans-intervertebral osteotomy with anterior support is potentially more secure than the conventional method for correcting ankylosing spondylitis kyphosis.